Universitas Pamulang Systematic Literatur Review : Analisis Sistem Informasi Penjualan - Aimi Saputra; Ines Heidiani Ikasari (Journal of Research and Publication Innovation, 2023)
Sales information system analysis is an important process in developing and maintaining an effective sales information system. In the ever-evolving digital era, a comprehensive understanding of methods, techniques and approaches related to sales information system analysis is very important. Therefore, this study aims to conduct a Systematic Literature Review (SLR) on sales information system analysis. This study follows a structured and systematic SLR methodology. Literature searches were conducted through databases of journals, conferences and other reliable sources. The focus of this research is the literature that discusses concepts, techniques, and approaches related to sales information system analysis. The findings of this study reveal several important things. First, various analytical methods are used in the context of sales information systems, including requirements analysis, business process analysis, data analysis, and security analysis. Second, there are frameworks and models that have been developed to guide the analysis of sales information systems, such as business process models, entity and relationship models, and data analysis models. In addition, this study also highlights the importance of stakeholder involvement in the sales information system analysis process. Through the participation and good understanding of stakeholders, the analysis results can be more relevant and can support the right decision making. However, this study also identified some challenges in sales information system analysis, such as high data complexity, coordination between different departments, and fast changing business requirements. Therefore, further research and development of better analytical methods are needed to overcome this obstacle. In conclusion, this study presents a comprehensive review of sales information system analysis using the Systematic Literature Review method. These findings provide an in-depth understanding of the methods, techniques and approaches related to the analysis of sales information systems. The results of this study can be a guide for practitioners, researchers and academics in analyzing and developing an effective sales information system. Â